Joining of aluminium alloy and galvanized steel using a controlled gas metal arc process. (June 2017) - Das, A.; Shome, M.; Goecke, Sven-F.; De, A.
Highlights: Mixed material joints of AA5754 and hot-dip galvanized steel sheets were achieved. A pulsed current gas metal arc process with short-circuiting metal transfer was used. Current and voltage transients were monitored to estimate real-time arc heat input. A heat input range of 36–106 J mm− 1 provided the best joint strength of 208 MPa. The interface layer with Fe-Al intermetallic compounds was restricted within 6.1 μm. Abstract: A precise control of the heat input is needed to restrict the development of Fe-Al brittle intermetallic compounds along the joint interface and the growth of the interface layer in mixed-material joints of aluminium and galvanized steel sheets. A novel study is presented here on the joining of aluminium alloys and galvanized steel sheets using a gas metal arc process with short-circuiting metal transfer and fast responsive control of current and voltage pulses. The influence of the processing conditions on the heat input, phase layer thickness, type of intermetallic compounds and joint strength is studied extensively. The permissible heat input is found to be in the range of 36–106 J mm− 1 that has led to 0.68–6.10 μm thick phase layers along the joint interface with the maximum joint strength of 208 MPa.